Living on the edge: Household vulnerability to food-insecurity in the Punjab, Pakistan. (October 2016) - Azeem, Muhammad Masood; Mugera, Amin W.; Schilizzi, Steven
Highlights: Households are likely to become food-insecure in the future not as a result of poor resource endowments but because of risk. The risk of household-specific shocks is higher compared to community-wide shocks. Urban dwellers appear to face higher risk of being food-insecure than rural. Abstract: This study investigates the prevalence, sources and distribution of household vulnerability to food-insecurity in the Punjab, Pakistan. Applying a multilevel model on a large dataset of about 90, 000 households, we find that the share of households at risk of becoming food-insecure (vulnerability) is higher than the share that is current food-insecure. Households in rural areas are least vulnerable. In contrast, residents of cities and urban areas experience high level of vulnerability that exceeds the average in the Punjab. The risk-induced vulnerability is higher than the structural-induced vulnerability and vulnerability to idiosyncratic shock is higher than vulnerability to covariate shocks. Findings imply that households in the Punjab are vulnerable not as a result of poor resource endowments but because of risk. The Pakistani government should go beyond mere observed food-insecurity to address the needs of the relatively larger population that is at risk of being food-insecure in the future.